Improving time estimation in JKR project - Hasan, Muhamad Khair (2010)
Accurate time estimation is very critical to ensure smooth operation and timely completion of any construction project delivery. In determining the time of the project completion the only known methodology currently used by JKR is based on prediction from the experience of completing past project. However evidently the project delay issues are very common for JKR projects. Many reasons contributed to this phenomenon. One of such reasons is that the time estimation process done by JKR might no be accurate. To understand further of such issue this study has been for carry out with the aim to determine the cause of the delay that lead with the slippage time from the original estimate. This study has benefited from thousands of data available from JKR SKALA’s database. Other methodologies adopted include the used of questionnaire survey distributed to JKR personnel and contractors. The findings of this study has determined the major factors that contributed to the delay. Comparisons was made for the findings from different sources. Factors that can contributed for improving JKR project time estimating process had also been identified. Various comparison have been made on the trend of the delay with regard to time factor, project size and location. The information generated from this study can provide a very useful guide for JKR in planning the more reliable project duration in future.